Sequential injection-capillary immunoassay system for determination of sialoglycoconjugates - Supaporn Kradtap Hartwell (2018)
An automatic immunoassay system for an assay of sialoglycoconjugates was developed based on the sequential injection technique. A cost effective plain glass capillary tube was used as a solid surface for immobilization of biomolecules via a simple physical adsorption which is adequate to tolerate the force of solution flowing through the capillary during the multi-steps immunoassay process. Immunoassay could be performed with many improvements-rapidity per sample as compared to the conventional micro-plate format (40 min vs. 5-8 h); lower cost and simpler as compared to fused silica capillary with covalent immobilization; and without problem of back pressure as compared to flow injection-bead based immunoassay. Performance of the sequential injection-capillary immunoassay was demonstrated by assay of sialoglycoconjugates level in human serum to differentiate cancer patients from healthy people. © 2009.